Quality of Life and Role of Palliative and Supportive Care for Patients With Brain Metastases and Caregivers: A Review - Wu, Adela; Colón, Gabriela Ruiz; Lim, Michael (Frontiers in Neurology, 2022)
ABSTRACT Brain metastases (BM) are the most commonly diagnosed secondary brain lesions in adults, influencing these patients’ symptoms and treatment courses. With improvements in oncologic treatments, patients with BM are now living longer with their advanced cancers, and issues pertaining to quality of life become more pressing. The American Society of Clinical Oncology has recommended early implementation of palliative care for cancer patients, though incorporation and implementation of palliative and other supportive services in the setting of true multidisciplinary care requires additional attention and research for patients with intracranial metastases. We review the physical, cognitive, and psychosocial challenges patients with BM and their caregivers face during their cancer course as well as the current published research on quality of life metrics relating to this patient population and the diverse roles specialty palliative care, rehabilitation services, and other healthcare providers play in a comprehensive multidisciplinary care model.